Studying Some Aspects of Rural Women’s Contribution in Rural Development in Lattakia Governorate - Hasan, Ibrahim (Latakia University Journal -Biological Sciences Series, 2013)
This study aims at identifying some aspects of women’s contribution in rural development in Lattakia Governorate. The research results show a decrease of 16.6% in the illiteracy rate in the sample studied, whereas the percentage of secondary school certificateholders reaches 31.4%. The results also show that the percentage of working women is 60%, the rest are housewives. In addition to that, the study indicates that 94.9% of women believe that education has great benefits, but they also believe that it is necessary to provide enough job opportunities for them. This is in order to activate their role in the process of rural development. Finally, the results indicate that there is a correlation between rural development on the one hand and the development of rural women on the other hand. They also show that women play a clear role in many educational, agricultural, health and living aspects, and that this role increases as the educational level of women increases.